International research progress and trend of transit-oriented development: An analysis of knowledge mapping based on cite space - Wu, Tao; Li, Mingjing (Frontiers in Environmental Science, 2022)
Transit-oriented development (TOD) which is regarded as one of the most successful planning methods for urban and transport sustainability, has garnered much attention from academics and planners. Despite the growing interest in TOD research, there has not been a comprehensive review of the knowledge structure, research hotspots and emerging trends about TOD research. This study aims to address the research gap by providing a bibliometric overview and visualization of the TOD research. Based on the bibliometric analysis methods, this study uses data collected from Web of Science (WOS) and uses CiteSpace software for visualizing and analyzing international research progress and trends in the TOD field. The results showed that publications on TOD research increased significantly, and most of the articles were published by the United States and China. Universities were the mainstays of the TOD research institutions, and the most productive authors were Dr. Ewing, Dr. Cervero, and Dr. Bertolini. The co-citation network analysis showed that the influential articles were published by Kamruzzaman, Vale, and Papa, and six main research area could be detected. The keyword co-occurrence network analysis displayed three stages for the evolution of TOD research, and popular topics in different stages were revealed. Three frontier hotspots were identified by the keywords burst analysis, namely oriented development, pattern, and typology.